PREVALENCE OF LATENT TUBERCULOSIS IN DIABETIC AND NON-DIABETIC INDIVIDUALS IN A TERTIARY CARE CENTER: A COMPARATIVE STUDY - KADAM, ROHAN; KUMAR, SUDEEP; KANAWADE, TUSHAR; RS, JOSHI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aims of this study were as follows: (1) To study the prevalence of latent tuberculosis (TB) in diabetic and non-diabetic population attending the tertiary care hospital. (2) To investigate the association between diabetes mellitus (DM) and latent TB, evaluating the prevalence of positive tuberculin tests and assessing glycemic parameters in diabetic patients with latent TB. Methods: This was a single-center, hospital-based, observational, and comparative study conducted in the department of general medicine of a tertiary care medical college. One hundred and thirty-six diabetic patients of either gender or 137 healthy individuals acting as control group were included in this study on the basis of a predefined inclusion and exclusion criteria. Patients were evaluated by detailed history and clinical examination. The diagnosis of latent TB was based on a positive tuberculin test without any clinical features of active TB. The prevalence of latent TB infection was compared in both the groups. p<0.05 was taken as statistically significant. Results: Patients in both the groups were found to be comparable in terms of gender distribution and mean age. Predominant patients were found to have type 2 DM. The mean duration of DM was noted to be 91.58±60.68 months. The most common diagnoses of patients in non-diabetes group were COVID-19 (9.49%), neurological diseases (8.76%), infections (7.3%), acute myocardial infarction (6.57%), and iron deficiency anemia (5.84%). About 21.32% of cases in DM group were noted to have latent TB, while the proportion of latent TB was noted to be 7.30% in the non-diabetes group. The mean fasting blood sugar, mean post-prandial blood sugar, as well as mean HbA1c were significantly higher (p<0.05) in the subgroup with latent TB versus the subgroup without latent TB. Conclusion: Individuals with diabetes mellitus were found to have increased risk of latent TB infection. In addition, male gender and elevated glycemic parameters were found to be key factors associated with latent tuberculous infection in diabetes.